The Relationship Between Onset-To-Treatment Time Interval and History of PCI Therapy With Triage Selection in The Cardiac Emergency Center For STEMI Patients - Yusuf Hanafiah; Tsania Ayu Zaharany; Annisa Pratiwi Gunawan; Dzikra Fitria Amita; Helza Risdianti; Aurelia Firstania; Sartika Rajagukguk; Muhammad Chairul Aris (STIKES Adi Husada, 2025)
STEMI remains the leading cause of cardiovascular mortality, demanding an integrated management system to save the myocardium, where the accuracy of triage decisions is the key determinant of timely access to cardiac catheterization. However, in practice, several clinical factors can complicate triage assessment, including variations in symptom presentation and specific patient characteristics. A prolonged onset-to-symptom interval often alters and obscures symptoms, while a history of prior Percutaneous Coronary Intervention (PCI) is not always clearly evident. This study employed an analytical observational design with a cross-sectional approach to analyze the correlation between independent and dependent variables. The study was conducted in the Cardiac Emergency Center (CEC) of Haji Adam Malik General Hospital during the period of September to December 2024. The study population consisted of all patients diagnosed with ST-Elevation Myocardial Infarction (STEMI). The sampling technique used was total sampling, yielding 86 respondents. Based on statistical testing, the correlation between STEMI onset time and triage category selection was found to be 0.003, indicating a significant correlation between the two variables. Meanwhile, the variable of PCI history with triage category selection had a significance value of 0.308, suggesting no correlation between the two variables. The onset-to-symptom interval is a factor significantly correlated with the selection of triage priority level in STEMI patients at the Cardiac Emergency Center. This reinforces the principle of â€œtime is muscleâ€ in STEMI management, where the duration from symptom onset to hospital arrival directly influences the assessment of severity and the determination of treatment priority by nurses.